2010
DOI: 10.4314/afrrev.v4i2.58288
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Values of Chrysophyllum Albidum Linn African Star Apple as a Domestic Income Plantation Species

Abstract: This study analyzed the nutritive composition of Chrysophyllum albidum Linn. It was necessitated by the need towards creating awareness that this species can provide nutrient supplements for the larger percentage of the population in the rural and peri-urban communities. Chrysophyllum albidum locally called "Udara" is one of the 80 species of Chrysophyllum Linn, a pan-tropical genus. Market Survey was done to collect data from three major markets in Rivers State known for assorted fruits business. Eight to ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 1 publication
0
13
0
Order By: Relevance
“…International center for research in agro-forestry (ICRAF, 2007) noted that the fleshy and juicy fruit which is popularly eaten is a potential fruit source for soft drink production. The fruits are also suitable for the production of fruit jams and jellies (Ureigho and Ekeke, 2010). Ajewole and Adeyeye (1991) reported that the juice of the fruit has potentials as an ingredient of soft drinks and can be fermented for wine or other alcohol production while Adepoju et al (2012) observed African Star Apple to be high in micronutrients of nutritional importance, low in gross energy, sodium and antinutrients, and possess excellent values of index of nutritional quality and suggested that their consumption by the populace should be encouraged and promoted where and when the fruit is available.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…International center for research in agro-forestry (ICRAF, 2007) noted that the fleshy and juicy fruit which is popularly eaten is a potential fruit source for soft drink production. The fruits are also suitable for the production of fruit jams and jellies (Ureigho and Ekeke, 2010). Ajewole and Adeyeye (1991) reported that the juice of the fruit has potentials as an ingredient of soft drinks and can be fermented for wine or other alcohol production while Adepoju et al (2012) observed African Star Apple to be high in micronutrients of nutritional importance, low in gross energy, sodium and antinutrients, and possess excellent values of index of nutritional quality and suggested that their consumption by the populace should be encouraged and promoted where and when the fruit is available.…”
Section: Introductionmentioning
confidence: 99%
“…It is called cherry by English natives, Agbalumo in the Southern-western part of Nigeria, Udara in the Eastern part of the country and Otien in Edo state. Ureigho and Ekeke (2010) estimated the proximate composition of Africa star apple to be in the range of 11% carbohydrate, 4% crude fiber, 3% Lipids ,7 % protein ,Calcium (17.11 ppm), Iron (<1 ppm), phosphorus (9.92 ppm), vitamin C (25.03 ppb), vitamin A (10.74 ppb), B1 and B2 (<1 ppb). The study recommended that the awareness of the nutritive value of this species be increase so as to encourage its consumption as food supplement and utilization.…”
Section: Introductionmentioning
confidence: 99%
“…Findings in this work are in agreement with Okafor, (1981;Dimelu and Odo, 2013) who observed that the species is an important agroforestry home garden species in southern Nigeria. Fresh fruit pulp has been reported to contain crude protein, vitamins, fibre, carbohydrate and micronutrients such as calcium, iron and phosphorus in reasonable quantities (Ureigho and Ekeke, 2010;Adepoju and Adeniji, 2012). Trade in Udara fruits when in season alleviates poverty by yielding substantial income to producers and marketers locally.…”
Section: Resultsmentioning
confidence: 99%
“…It is also an excellent source of vitamins B and D as well as iron [4]. Umoh [5] and Ureigho [6] reported on the proximate composition, minerals and vitamins content of Chrysophyllum albidum.…”
Section: Introductionmentioning
confidence: 99%
“…The fruits contain 90% anacadic acid, which is used industrially in protecting wood and as a source of resin. The fruits can be used in the preparation of wine, soft drink, jams and jellies [3,6].…”
Section: Introductionmentioning
confidence: 99%